2013
DOI: 10.1080/00131911.2012.679915
|View full text |Cite
|
Sign up to set email alerts
|

Parents of excluded pupils: customers, partners, problems?

Abstract: In this paper we present new data from interviews with parents of pupils permanently excluded from alternative provision in England, and related service providers. We report the social contexts of the families, their experience of 'choice', and how service providers talk about them. Our findings support those from earlier studies in relation to the disadvantage experienced by many parents. As predicted, the parents experienced choice as very limited. Some parents, due to a lack of personal, social or economic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…While such intentions are commonly seen in international policy discourse, their translation in practice is far more complex, and has been addressed differently in various national contexts. Even in England, where special educational needs (SEN) legislation positions parents as partners in the education of their child (Department for Education, 2014), research highlights how parents are more likely to be seen as customers or a problem by the local education authorities and schools (Macleod et al, 2013). Additionally, studies exploring parental decision making on school choice have concluded the lack of real choice for parents, particularly those from minority ethnic groups (Crozier and Davies, 2007;Byrne, 2013).…”
Section: Introductionmentioning
confidence: 98%
“…While such intentions are commonly seen in international policy discourse, their translation in practice is far more complex, and has been addressed differently in various national contexts. Even in England, where special educational needs (SEN) legislation positions parents as partners in the education of their child (Department for Education, 2014), research highlights how parents are more likely to be seen as customers or a problem by the local education authorities and schools (Macleod et al, 2013). Additionally, studies exploring parental decision making on school choice have concluded the lack of real choice for parents, particularly those from minority ethnic groups (Crozier and Davies, 2007;Byrne, 2013).…”
Section: Introductionmentioning
confidence: 98%
“…While Riddell and Weedon (2010) portray hostile local authority professionals, intent on protecting their hegemonic professionalism, and parents who suffer at their hands, others argue that the complex relationships between parents and professionals rather reveal 'the fault-lines of some of the key tenets of contemporary social policy' (Macleod et al, 2012), including those in the marketisation and personalisation of services. Both parents and professionals are subjected to and often constricted by the performative demands made on them.…”
Section: Models Of Partnership Workingmentioning
confidence: 99%
“…Two contrasting views on the continuing challenges in parent-partnerships Professionals often view parents as 'well-intentioned but ill-equipped' (Macleod et al, 2012) in terms of their advocacy role. While parents are credited with having the best interests of their child at heart, they are frequently seen as unable to promote those interests because of their own emotional needs, and as being either too limited (in terms of their personal, social or economic resources) or too demanding and unrealistic.…”
Section: Models Of Partnership Workingmentioning
confidence: 99%
See 1 more Smart Citation
“…There is also small scale and anecdotal evidence of some academies being reluctant to accept pupils with significant special needs (Institute of Public Policy Research 2014 cited by Norwich and Black 2015, 131) or re-locating them within an academy group or chain (Perraudin 2016). Macleod, Pirrie, McCluskey and Cullen (2013), writing of pupils who have been excluded from specialist provision, point out that choice is complicated in relation to pupils with SEN and largely illusory for pupils with a history of challenging behaviour and exclusion (389).…”
Section: Literature Reviewmentioning
confidence: 99%